2020
DOI: 10.7600/jpfsm.9.37
|View full text |Cite
|
Sign up to set email alerts
|

Effects of static stretching on active muscle stiffness with and without the stretch reflex

Abstract: The purpose of the present study was to examine acute changes in active muscle stiffness with and without the stretch reflex following static stretching. Before and after static stretching for 10 min, active muscle stiffness was measured according to changes in exerted torque and fascicle length during short-range stretch of faster (peak angular velocity of 250 deg•s-1 ; without the stretch reflex) and slower (peak angular velocity of 100 deg•s-1 ; with the stretch reflex) angular velocities. During the measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…However, to explore the relationship between joint stiffness and muscle mechanical properties during exercise, it is necessary to examine muscle stiffness under active rather than passive conditions. We devised a method to quantify the stiffness of the medial gastrocnemius muscle under active conditions, i.e., active muscle stiffness (Kubo, 2014 ), and conducted various intervention studies (Kubo et al, 2017 , 2021 ; Kubo & Ikebukuro, 2019 ; Suzuki et al, 2020 ). Our recent studies demonstrated that joint stiffness and active muscle stiffness transiently decreased after repeated hopping exercises and increased with 12 weeks of plyometric training, although tendon stiffness did not change with either intervention (Kubo et al, 2017 , 2021 ; Kubo & Ikebukuro, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, to explore the relationship between joint stiffness and muscle mechanical properties during exercise, it is necessary to examine muscle stiffness under active rather than passive conditions. We devised a method to quantify the stiffness of the medial gastrocnemius muscle under active conditions, i.e., active muscle stiffness (Kubo, 2014 ), and conducted various intervention studies (Kubo et al, 2017 , 2021 ; Kubo & Ikebukuro, 2019 ; Suzuki et al, 2020 ). Our recent studies demonstrated that joint stiffness and active muscle stiffness transiently decreased after repeated hopping exercises and increased with 12 weeks of plyometric training, although tendon stiffness did not change with either intervention (Kubo et al, 2017 , 2021 ; Kubo & Ikebukuro, 2019 ).…”
Section: Introductionmentioning
confidence: 99%